Mitochondrial Polymorphisms Are Associated Both with Increased and Decreased Longevity - Castri, Loredana (S. Karger AG, 2009)
Previous work compared frequency of longevity-associated polymorphisms (LAPS) in long-lived individuals and in controls from the general population (primarily in Europe and Japan), suggesting the polymorphisms are responsible for unusual longevity. However, individuals from the general population are not the control group for long-lived subjects because both were born in different periods. We report results of a project which collected mtDNA from living subjects in Costa Rica, and traced back their maternal genealogy. Since mtDNA does not recombine and its probability of mutation is low, we can assume that the maternal ancestors had the same mtDNA of their descendants. We compared the longevity of individuals with LAPS with the longevity of controls born in the same time period. We did not confirm previous associations for several markers, but found that the 5178A mutation in haplogroup D is associated with decreased longevity, whereas the 150T mutation is associated with increased longevity. These associations however, are not significant for all time periods under study. While our data confirm that mtDNA make up affects longevity, they also indicate that the time period in which a person was born had a much greater impact on longevity than presence or absence of a marker.